The Relationship between Perfectionism, Stress and Burnout in Male and Female Swimming Coaches - Hasan Mohammadzadeh; Samko Ebrahimi; Saadi Sami (University of Tehran, 2012)
The aim of this research was to investigate the relationship of perfectionism, stress and burnout in male and female swimming coaches. For this purpose, 154 coaches (85 men with the mean age of 30.52±5.26 years and 7.69±4.96 years of coaching experience and 69 females with the mean age of 28.82±5.16 years old and 4.46±6.40 years of coaching experience) were selected. For data collection, four questionnaires were used: Personal information, Hill et al. (2004) perfectionism, Coudron stress and Burnout questionnaire of Maslach and Jackson (1996). To analyze the data, descriptive statistics were used to design tables and diagrams and distribution indicators like mean, median and mode were used. Also inferential statistics were used at (P